Pendampingan Komunitas Pembatik Melalui Pelatihan Alih Pengetahuan Membatik dengan Material Berbasis Kearifan Lokal - Ariesa Pandanwangi; Ida; Olga Catherina Pattipawaej; Erwani Merry Sartika (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2019)
Indonesia is very rich in local wisdom, various types of plants can be processed into batik materials, one of which is tamarind tree which has not been widely known by many people. Tamarind seeds can be processed into a kind of cold wax, not hot wax. In the practice of traditional batik, this material is then used in community service activities with the aim of introducing how to make batik through batik workshop using cold wax easily and environmentally friendly. Participants in this workshop were foreign students and other people by using lectures method, batik demonstrations, and batik practices. To test the success of participants in batik knowledge and practice, the researcher used paired samples test. Based on the analysis, it can be said that there are differences in the knowledge of participants before and after community service activities. The aim of assistance was achieved because the transfer knowledge was successful, supported by the results of the trainer's questionnaire evaluation in terms of mastery of the material, clarity of material delivery, and appropriateness of time allocation.